2013
DOI: 10.1111/iju.12277
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after radical nephrectomy: Development and validation of predictive models in Japanese patients

Abstract: Abbreviations & AcronymsObjectives: To develop and validate predictive models for postoperative estimated glomerular filtration rate and risk of chronic kidney disease after radical nephrectomy in Japanese patients. Methods: The present retrospective study included a development cohort of 209 patients without preoperative chronic kidney disease who underwent radical nephrectomy between 1994 and 2008, and were followed up for longer than 3 years, and a validation cohort of 144 similar such patients. Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
4
21
0
1
Order By: Relevance
“…The association between CKD development and poorer baseline kidney function is also well known . In the present study, preoperative eGFR was the only variable found to have a significant interaction with nephrectomy type, such that even those with relatively high eGFR measures preoperative (70‐79 mL/min per 1.73 m 2 ) who underwent RN were substantially more likely to develop new CKD than those with lower preoperative eGFR (60‐69 mL/min per 1.73 m 2 ) who underwent PN.…”
Section: Discussionmentioning
confidence: 44%
“…The association between CKD development and poorer baseline kidney function is also well known . In the present study, preoperative eGFR was the only variable found to have a significant interaction with nephrectomy type, such that even those with relatively high eGFR measures preoperative (70‐79 mL/min per 1.73 m 2 ) who underwent RN were substantially more likely to develop new CKD than those with lower preoperative eGFR (60‐69 mL/min per 1.73 m 2 ) who underwent PN.…”
Section: Discussionmentioning
confidence: 44%
“…Our findings dovetail with a recent report by Isharwal et al [25] demonstrating that comorbidity status fails to predict renal functional decline after renal surgery. The literature in this space is contradictory [23,26,27], but the greatest predictor of eGFR decline to ≤45 mL/min/1.73 m 2 remains RN [28,29]. Woldu et al [30] recently compared renal functional outcomes after NSS and RN among patients with CKD I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Yokoyama et al [30] first reported the equation to predict eGFR 3 years after RN. They showed age, presence of diabetes mellitus, and preoperative eGFR were significant predictors of postnephrectomy eGFR.…”
Section: Discussionmentioning
confidence: 99%